2008
DOI: 10.1016/j.neuropsychologia.2008.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Different constraints on grip selection in brain-damaged patients: Object use versus object transport

Abstract: The present study discusses the presence of different constraints on action selection during object use versus object transport. Sixteen left brain-damaged (LBD) patients, 10 right brain-damaged (RBD) and 35 healthy controls were examined on a grip preference test consisting of a grasping-to-transport and a grasping-to-use condition. Assessment included a general praxis testing (pantomime production, object utilization gesture recognition and object use). We also reported the case of a close-head injury patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 13 publications
(17 reference statements)
1
41
2
Order By: Relevance
“…Goal postures can be planned first but subsequent movement planning can feed back to the goal posture level, leading to a different goal posture if necessary. Consistent with this hypothesis, movement paths can influence choices of goal postures (Elsinger & Rosenbaum, 2003; Osiurak et al, 2008). …”
mentioning
confidence: 66%
“…Goal postures can be planned first but subsequent movement planning can feed back to the goal posture level, leading to a different goal posture if necessary. Consistent with this hypothesis, movement paths can influence choices of goal postures (Elsinger & Rosenbaum, 2003; Osiurak et al, 2008). …”
mentioning
confidence: 66%
“…Behavioral research has provided support for a left hemisphere dominance in the motor planning of end-state comfort effects in right and left handers (Janssen et al, 2011). It remains a matter of debate whether the planning of reach and grasp actions for object use versus object transport are guided by different mechanisms (Osiurak et al, 2008). In addition to reach-and-grasp planning, we also must recall and apply the appropriate object-related movements to achieve the planned goal.…”
Section: Usingmentioning
confidence: 99%
“…This is less comfortable than grasping them with non inverted hand but leads without detour to the optimal hand position for use. When, however, the purpose of grasping is transport rather than use of the tool most subjects grasp with the noninverted hand . As we discussed in the previous section for the pantomime of grasping a glass, the adaptation of grip to the structural properties of the grasped object is accomplished by visuo‐motor mechanisms that are not affected by apraxia.…”
Section: Use Of Tools and Objectsmentioning
confidence: 99%
“…They did indeed demonstrate that some patients with left brain damage grasp tools pointing toward them with noninverted hands even when they are instructed to demonstrate their use but there is no clear relationship between this lack of motor planning and apraxia for tool use. A majority of patients who commit errors of tool use nonetheless adapt their grip to the orientation of the tool while on the other hand there are patients who disregard subsequent use for grip selection but succeeded in demonstrating correct use of the awkwardly grasped tools . Moreover, lesion analysis revealed that different left hemisphere lesions were responsible for selection of grips and for correct use …”
Section: Use Of Tools and Objectsmentioning
confidence: 99%